Serum Selenium Levels in Type 2 Diabetes Mellitus Patients - Baneen Sami Tarif; Zainab Hussein AL-Hellawi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Diabetes mellitus type 2 (T2DM) is a long-term metabolic disorder characterized by high blood glucose levels. T2DM is caused by insufficient insulin secretion by pancreatic β-cells and an inability of insulin-sensitive tissues to respond appropriately to insulin. In 2019, there are over 463 million people worldwide who have T2DM. Sixty T2DM patients and thirty healthy people served as controls. In terms of age and body mass index (BMI), these patients were comparable to a control group. This study determined demographics and serum selenium (Se). The findings of this study indicated a significant decrease in serum Se in T2DM patients compared to the healthy group. Many T2DM complications are caused by uncontrolled blood glucose and a decrease in antioxidant agents. Increased HbA1c is associated with an increased risk of serious microvascular and macrovascular complications. Low Se levels, on the other hand, increase reactive oxygen species (ROS), and Se deficiency is linked to a number of cardiovascular diseases, including myocardial infarction, cardiomyopathy, atherosclerosis, and coronary heart disease.